Implementing Kahoot-assisted Team-Assisted Individualization (TAI) Cooperative Learning on Mathematics Problem-Solving Skills and Self-Confidence in Junior High School Students - Vina Pebrianti (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2025)
This study aims to determine the effect of the Team Assisted Individualization (TAI) cooperative learning model assisted by Kahoot on students' mathematical problem-solving abilities and self-confidence. The method used is a mixed method, with an embedded model design. The research subjects were 8th-grade students at SMP Pasundan 3 Bandung. The instruments used were problem-solving ability tests and a Likert-scale self-confidence questionnaire. The results indicated that students who learned through the Kahoot-assisted TAI model experienced significantly greater improvements in mathematical problem-solving skills and self-confidence than those who received conventional instruction. These results indicate that integrating cooperative learning with a gamified digital platform can effectively enhance students' cognitive and affective learning outcomes.